2019
DOI: 10.1021/acsaem.9b00717
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanosecond Laser Beam Shaping on Cu(In,Ga)Se2 Thin Film Solar Cell Scribing

Abstract: The Cu­(In,Ga)­Se2 (CIGS) thin film solar cell is a promising material architecture considering its high photovoltaic (PV) efficiency at low material cost. Recently, the authors demonstrated all laser based mini-module fabrication on a transparent conducting oxide (TCO) based CIGS architecture, using a cost-effective nanosecond laser beam illuminated from the transparent glass substrate side. While indium tin oxide (ITO) is a promising TCO to this end, allowing ohmic contact with CIGS and low sheet resistance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Employing a 64 µm beam spot size overcame this issue with the added benefit of increased scanning speeds. Moreover, using an elliptical shaped beam (21 µm × 84 µm) could suppress ITO damage, accompanied by narrower width, more straight grooves, and higher scanning speeds [65]. A similar induced ablation study using a ps laser confirmed the advantage of using an elliptical beam for selective film removal and high-quality scribes.…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…Employing a 64 µm beam spot size overcame this issue with the added benefit of increased scanning speeds. Moreover, using an elliptical shaped beam (21 µm × 84 µm) could suppress ITO damage, accompanied by narrower width, more straight grooves, and higher scanning speeds [65]. A similar induced ablation study using a ps laser confirmed the advantage of using an elliptical beam for selective film removal and high-quality scribes.…”
mentioning
confidence: 70%
“…Moreover, lift-off ablation can be a great fit for scribing the CIGS absorber layer due to its high sensitivity to heat-induced damage even with ultrashort lasers; rear-side ablation with pressure through the Mo layer can be beneficial in this case [32]. Furthermore, new findings regarding this process indicate that enlarged laser beams may be used to avoid damage to the ITO because of the lower absorber-ITO interfacial temperature in P2-induced ablation [65].…”
Section: Microstructure and Surface Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…However, such a challenge could be efficiently addressed via fine-tuning of pulse energy (0.1–0.5 W of laser power) and scribing speed (10–110 mm/s) using an elliptical shaped laser beam (Figure S7). While using the elliptical laser beam, the longer axis was aligned along the laser scan direction toward enhanced pulse overlap enabling increased scribing speed, , whereas the shorter axis maintained the narrow scribing width. Detailed mechanisms are under investigation.…”
Section: Resultsmentioning
confidence: 99%